2022
DOI: 10.3390/genes13050757
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability of Inflammation and Oxidative Stress Genes Affects Onset, Progression of the Disease and Survival of Patients with Amyotrophic Lateral Sclerosis

Abstract: Inflammation and oxidative stress are recognized as important contributors to amyotrophic lateral sclerosis (ALS) disease pathogenesis. Our aim was to evaluate the impact of selected single-nucleotide polymorphisms in genes involved in inflammation and oxidative stress on ALS susceptibility and modification. One-hundred-and-eighty-five ALS patients and 324 healthy controls were genotyped for nine polymorphisms in seven antioxidant and inflammatory genes using competitive allele-specific PCR. Logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 81 publications
1
6
0
Order By: Relevance
“…In this work, we have shown that modulation of gzmA can regulate some pro-inflammatory cytokines and one oxidative stress enzyme, suggesting that several pathways involved in the pathogenesis of ALS could be targeted when modulating gzmA. Supporting our results, a previous study reported that genetic variability of both inflammation and oxidative stress genes can affect the onset and the course of the disease in patients with ALS [ 59 ]. However, modulation of the immune system is challenging, as we have demonstrated in this study that a complete suppression of gzmA did not show the best results, but a partial reduction of gzmA was sufficient to modulate the gzmA-dependent pro-inflammatory cytokine response.…”
Section: Discussionsupporting
confidence: 87%
“…In this work, we have shown that modulation of gzmA can regulate some pro-inflammatory cytokines and one oxidative stress enzyme, suggesting that several pathways involved in the pathogenesis of ALS could be targeted when modulating gzmA. Supporting our results, a previous study reported that genetic variability of both inflammation and oxidative stress genes can affect the onset and the course of the disease in patients with ALS [ 59 ]. However, modulation of the immune system is challenging, as we have demonstrated in this study that a complete suppression of gzmA did not show the best results, but a partial reduction of gzmA was sufficient to modulate the gzmA-dependent pro-inflammatory cytokine response.…”
Section: Discussionsupporting
confidence: 87%
“… 273 These genes have been discussed in multiple reviews recently. 273 , 274 We will not discuss them in depth.…”
Section: Probable Inducers Of Inflammation In Neurodegenerationmentioning
confidence: 99%
“…In this regard, recently new polymorphisms in the gene encoding IL-1β and in genes involved in oxidative stress ( e.g. , SOD2) have been identified as modifiers of ALS progression ( 153 ). IL-1β is one of the main biomarkers of inflammation in ALS ( 151 , 152 ).…”
Section: Il-1 Family Molecules In Other Main Neurodegenerative Diseasesmentioning
confidence: 99%